Citra Tokoh Perempuan dalam Kumpulan Dongeng Klasik Nusantara oleh Cerviana Susilo: Female Character Portrayal in The Kumpulan Dongeng Klasik Nusantara by Cerviana Susilo - Liasna, Tanita (Universitas Tidar, 2025)
Women in society are stereotypically portrayed as captivating, beautiful, gentle, empathetic, and caring figures, emotional, and maternal, but also perceived as weak, foolish, slow, and unable to make logical and quick decisions. Meanwhile, men are considered as figures who can make logical decisions easily, brave, powerful, strong, intelligent, wise, and independent. The images that emerge for women and men occur due to the concept of gender, which is a trait that is inherent in both men and women that is socially and culturally constructed. This study aims to find the image of female figures contained in the kumpulan Dongeng Klasik Nusantara oleh Cerviena Susilo and identify the implications of discussing kumpulan Dongeng Klasik Nusantara oleh Cerviena Susilo on Indonesian language and literature learning in schools. The method used is descriptive qualitative analysis. The results show that the image of women that emerges is the self-image of women and the social image of women. The self-image of women is divided into two parts: the physical image of women and the psychological image of women, while the social image of women is divided into the image of women in the family and the image of women in society.